ANALISIS PERENCANAAN BUKIT BUATAN (ESCAPE HILL) TERHADAP TINGGI RUN UP UNTUK TEMPAT EVAKUASI SEMENTARA - Windy Widilestari; Munirwansyah Munirwansyah; Halida Yunita (Prodi Magister Teknik Sipil Unsyiah, 2019)
As we know, there is still a lack of the optimal effort for temporary evacuation sites to face the various threats of the earthquake which may caused the tsunami in the city of Banda Aceh. To deal with this serious threat, it is necessary to prepare a place of salvation to face the tsunami. In this case, it is an escape hill. The objective of this research is to determine the bearing capacity of the subgrade to the escape hill planning and the amount of the settlement, due to the load of the embankment height (Hcrit) and the value of the slope safety factor (FK). This research is conducted in Desa Deah Baro with the GCS coordinates (Geographic Coordinate System) 5º33'45.72